Application of Google Earth Engine to Estimate the Water Capacity of Saigon–Dongnai Basin in the Period of 2005–2023 Using MODIS and CHIRPS Satellite Data - Trong Dieu Hien, Le; Le Tan Dat, Nguyen (VNU Journal of Science: Earth and Environmental Sciences; Vol 41 No 1DO - 10.25073/2588-1094/vnuees.5215, 2025)
This study used the Google Earth Engine (GEE) platform to calculate the water capacity of the Saigon-Dongnai basin using remote sensing-derived products related to evapotranspiration (ET) and precipitation (P). The GEE was used to retrieve two important inputs: MODIS evapotranspiration spanning the drainage basin and CHIRPS satellite precipitation. We found that there was a net decrease in the water capacity from January to April every year as a result of greater evaporation and less precipitation. Due to the increase of precipitation from May to October following the decrease of solar radiation, and the drop in temperature, the rainy season imposed the highest values of the change in water capacity. Rainfall and evapotranspiration show a positive association, as does the relationship between water capacity and inputting water.